2020
DOI: 10.1177/1591019920949674
|View full text |Cite
|
Sign up to set email alerts
|

Direct angioplasty for acute ischemic stroke due to intracranial atherosclerotic stenosis-related large vessel occlusion

Abstract: Background Intracranial artery atherosclerotic stenosis (ICAS) is among the causes of intracranial large artery occlusion (LVO). The optimal treatment strategy for patients with ischemic stroke due to ICAS-related LVO remains unclear. In this retrospective case series, we discussed our experience with direct angioplasty as frontline therapy for ICAS-related LVO. Methods We extracted data for patients who had a known pre-existing ICAS and undergone direct angioplasty as frontline therapy for ICAS-related LVO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[4][5][6] In this setting, aggressive management, including acute antiplatelet therapy and intracranial angioplasty or stent placement, has been reported. [8][9][10]19,[22][23][24][25] These pharmacologic and mechanical approaches are most often combined with promising results, considering the specific largevessel occlusion stroke subtype. To date, the optimal pharmacologic adjunctive therapy for this recently described rescue approach for refractory intracranial occlusion is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In this setting, aggressive management, including acute antiplatelet therapy and intracranial angioplasty or stent placement, has been reported. [8][9][10]19,[22][23][24][25] These pharmacologic and mechanical approaches are most often combined with promising results, considering the specific largevessel occlusion stroke subtype. To date, the optimal pharmacologic adjunctive therapy for this recently described rescue approach for refractory intracranial occlusion is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The use of a retrieval stent as the first approach to LVO with underlying atherosclerosis has been discussed previously. [8][9][10] In case 2, the patient received PTA for residual stenosis after thrombectomy. Since the crab crow sign [11] was found at the occlusion site, thrombectomy was initially performed.…”
Section: Discussionmentioning
confidence: 99%
“…e primary cause of ischemic cerebrovascular disease and transient ischemic attack (TIA) in China is intracranial atherosclerotic stenosis (ICAS) [1,2]. e results of the 2014 CICAS study showed that 46.6% of patients with ischemic stroke and TIA in China had atherosclerosis and that patients with combined ICAS had severe symptoms and a high recurrence rate during the follow-up period [3,4].…”
Section: Introductionmentioning
confidence: 99%